Teenagers' Internet Use and Family Rules: A Research Note. - Wang, Rong; Bianchi, Suzanne M.; Raley, Sara B. (Journal of Marriage & Family, 2005)
The Internet poses challenges to parents who want their children to take advantage of online resources but also want to protect their children from questionable content. Using data from 749 dyads of American parents and their teenage children with Internet access, this study finds that the majority of parents report regulating their teenage children's Internet use, but parents report more monitoring (61%) than teens report (38%). Multivariate regression analyses indicate fathers, younger parents, parents who use the Internet with their children, and parents with younger teens engage in a higher level of parental monitoring. This study provides a first look at parental monitoring of children's Internet use and points to the need to study family rules from both parents' and children's perspectives. Reprinted by permission of the publisher.